Que aspectos subjetivos interferem na forma de lidar com as finanças tendo como base o atendimento a clientes: Psicologia & Economia Banco do Estado do Rio Grande do Sul S.A - Banrisul Agência Duque de Caxias - Fernandes, Cleide Antonio (Universidade do Vale do Rio dos Sinos, 2011)
This paper aims to trace the route that features the birth of economic psychology and behavioral economics as specific disciplines, their lines of research, possibilities of action and some prominent authors such as Antonio Zilhao, Vera Rita de Mello Ferreira and Tversky and Kanemann. It draws attention to the presence of this research, still less known in Brazil, propose alternatives to extend the field here that, in combination with psychoanalysis.We conducted this research, based on an agency Banrisul, with an audience of politicians, which is very demanding. The method used were questionnaires for internal customers, the bank's own employees and external. More important is the method of participant observation.The theme seeks to analyze the psychology of proximity to the area of finance, nursing care to clients in decision making, seeking to highlight emotional factors that interfere in financial negotiations. The theoretical approach and its interference in the economy and psychology determines how the decisions and the financial negotiations are conducted with the backdrop of emotional issues and non-rational.
Keywords: Economia; Emocional; Atendimento; Economy; Emotional care